Global evidence of gender inequity in academic health research: a living scoping review protocol. Issue 10 (10th October 2020) - Tricco, Andrea C.; Lachance, Chantelle C.; Rios, Patricia; Darvesh, Nazia; Antony, Jesmin; Radhakrishnan, Amruta; Anand, Sonia S.; Baxter, Nancy; Burns, Karen E. A.; Coyle, Doug; Curran, Janet A.; Fiest, Kirsten; et al.
ABSTRACT: Objective: The objective of this review is to describe the global evidence of gender inequity among individuals with appointments at academic institutions that conduct health research, and examine how gender intersects with other social identities to influence outcomes. Introduction: The gender demographics of universities have shifted, yet the characteristics of those who lead academic health research institutions have not reflected this change. Synthesized evidence will guide decision-making and policy development to support the progress of gender and other under-represented social identities in academia. Inclusion criteria: This review will consider any quantitative, qualitative, or mixed methods primary research that reports outcome data related to gender equity and other social identities among individuals affiliated with academic or research institutions that conduct health research, originating from any country. Methods: The JBI Manual for Evidence Synthesis and the Cochrane Collaboration's guidance on living reviews will inform the review methods. Information sources will include electronic databases, unpublished literature sources, reference scanning of relevant systematic reviews, and sources provided by experts on the research team. Searches will be run regularly to monitor the development of new literature and determine when the review will be updated. Study selection and data extraction will be conducted by two reviewers working independently, and all discrepancies will be resolved by discussion or a third reviewer. Data synthesis will summarize information using descriptive frequencies and simple thematic analysis. Results will be reported using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension to scoping reviews. Registration: Open Science Framework: https://osf.io/8wk7e/